Caffeic Acid Phenethyl Ester and Its Amide Analogue Are Potent Inhibitors of Leukotriene Biosynthesis in Human Polymorphonuclear Leukocytes - Boudreau, Luc H. (Public Library of Science, 2012)
BACKGROUND: 5-lipoxygenase (5-LO) catalyses the transformation of arachidonic acid (AA) into leukotrienes (LTs), which are important lipid mediators of inflammation. LTs have been directly implicated in inflammatory diseases like asthma, atherosclerosis and rheumatoid arthritis; therefore inhibition of LT biosynthesis is a strategy for the treatment of these chronic diseases. METHODOLOGY/PRINCIPAL FINDINGS: Analogues of caffeic acid, including the naturally-occurring caffeic acid phenethyl ester (CAPE), were synthesized and evaluated for their capacity to inhibit 5-LO and LTs biosynthesis in human polymorphonuclear leukocytes (PMNL) and whole blood. Anti-free radical and anti-oxidant activities of the compounds were also measured. Caffeic acid did not inhibit 5-LO activity or LT biosynthesis at concentrations up to 10 µM. CAPE inhibited 5-LO activity (IC(50) 0.13 µM, 95% CI 0.08–0.23 µM) more effectively than the clinically-approved 5-LO inhibitor zileuton (IC(50) 3.5 µM, 95% CI 2.3–5.4 µM). CAPE was also more effective than zileuton for the inhibition of LT biosynthesis in PMNL but the compounds were equipotent in whole blood. The activity of the amide analogue of CAPE was similar to that of zileuton. Inhibition of LT biosynthesis by CAPE was the result of the inhibition of 5-LO and of AA release. Caffeic acid, CAPE and its amide analog were free radical scavengers and antioxidants with IC(50) values in the low µM range; however, the phenethyl moiety of CAPE was required for effective inhibition of 5-LO and LT biosynthesis. CONCLUSIONS: CAPE is a potent LT biosynthesis inhibitor that blocks 5-LO activity and AA release. The CAPE structure can be used as a framework for the rational design of stable and potent inhibitors of LT biosynthesis.